FOSSO DELLA FITTAIA: THE OLDEST TUSCO-SARDINIAN LATE MIOCENE ENDEMIC VERTEBRATE ASSEMBLAGES (BACCINELLO-CINIGIANO BASIN, TUSCANY, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
The late Miocene continental successions of the Baccinello-Cinigiano basin (Grosseto), one of the longest and most continuous vertebrate-bearing continental successions in the Neogene Italian record, yielded at least four superimposed vertebrate assemblages bracketed in the time span 8.3 - 6.4 Ma. The Baccinello-Cinigiano basin is famous for recording endemic vertebrate assemblages that include the youngest European Miocene hominoid, Oreopithecus bambolii. The late Miocene endemic vertebrate fauna known as the Baccinello V0 assemblage is the oldest vertebrate fauna within the Baccinello-Cinigiano basin succession, being correlated to the European mammal Neogene unit MN11. Recent field surveys along the Trasubbie river allowed studying in detail the basal Baccinello-Cinigiano sedimentary succession, and sampling fossiliferous level bearing microvertebrates along the small creek Fosso della Fittaia. The sample “Fosso della Fittaia 2013” yielded about 170 fossil remains improving our documentation of the oldest vertebrate assemblages from the Baccinello-Cinigian basin. As far as rodents are concerned, in addition to the already recognized murid Huerzelerimys and glirid Anthracoglis, a few dental remains are assigned to a new genus and species of giant dormouse. It is further worth noting the occurrence in the sample of shrew remains (the first described from the Baccinello-Cinigiano basin) identified as cf. Lartetium. The latter attests the presence of a crocidosoricine in the Fosso della Fittaia 2013 assemblage, postdating the youngest known occurrences of the subfamily by at least 1 my. The vertebrate assemblage is completed by a diverse herpetofauna and the first fish remains reported from the basin.